Criminal Responsibility for the Dissemination of Discrediting Materials Concerning the Armed Forces According to the Russian Criminal Code - Georgii Sibirtsev (Nordicum-Mediterraneum)
This article considers criminal responsibility for the dissemination of discrediting materials of the armed forces of the Russian Federation. The academic paper is a legislative analysis of the law of the Russian Federation of 2022 prohibiting the „discreditation and dissemination of armed forces of the Russian Federation.” Based on the analysis of the elements of crime, the author puts forward a hypothesis about the controversial and subjective matter of the novelisation. The imprecise terminology and definitions of the discussed legal act introducing such criminal responsibility, allow the law enforcement agencies to punish any opinion which somehow differs from the official narration. In addition, the historical roots of this prohibition are considered. The article provides comprehensive review of the judicature practice of Russian courts.